Faktor-faktor yang mempengaruhi Teknologi Pengurangan Intensitas Kebisingan pada Pesawat: Sistem, Desain dan Resiko - Safura, Adinda; Sanjaya, Rizky Aminah Handayani; Sunardi , Sunardi; Septiani, Virma; Andayani, Thursina (Journal of Engineering and Transportation, 2024)
The effect of aircraft operations at the airport is noise. Noise is a loud sound whose frequency is excessive and undesirable, so that it has an effect on physical conditions and psychology such as hearing loss and other health hazards. To reduce the intensity of noise that can have a negative impact on health, there are efforts that can be made by applying noise reduction technology on aircraft. In determining aircraft noise reduction technology, there are several factors that need to be considered such as the system, design, and risks that can occur if you ignore the application of the technology, therefore this article reviews it. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The research method used in this research is literature review based on several journals and previous related research. The results of this study are: 1) System affects aircraft noise reduction technology; 2) Design affects aircraft noise reduction technology; and 3) Risk affects aircraft noise reduction technology. This research is expected to be a reference for further researchers in the field of industrial technology, especially aviation.